The Effect of Crack Width on Chloride-Induced Corrosion of Steel in Concrete - Weiwei Li; Weiqing Liu; Shuguang Wang (Advances in Materials Science and Engineering, 2017)
When subjected to loading or thermal shrinkage, reinforced concrete structures usually behave in a cracking state, which raises the risk of bar corrosion from the working environment. The influence of cover cracking on chloride-induced corrosion was experimentally investigated through a 654-day laboratory test on cracked reinforced concrete specimens exposed to chloride solution. The concrete specimens have a dimension of 100 mm × 100 mm × 400 mm and a single prefabricated crack at the midspan. When the percentage concentration of chloride ion (0.6%, 1.2%, 2.1%, 3.0%, and 6.0%) and crack width (uncracked, 0.2, 0.3, 0.4, and 0.5 mm) are taken as variables, the experimental results showed that the corrosion rates for cracked specimens increased with increasing percentage concentration of chloride and increasing crack width. This study also showed the interrelationship between crack width and percentage concentration of chloride on the corrosion rate. In addition, an empirical model, incorporating the influence of the cover cracking and chloride concentration, was developed to predict the corrosion rate. This model allows the prediction of the maximum allowable wcr based on the given percentage concentration of chloride in the exposure condition.